ARAH PERKEMBANGAN SISTEM PEWARISAN ADAT BALI PASCA BERLAKUNYA KEPUTUSAN PESAMUHAN AGUNG MUDP BALI NOMOR 01/KWP/PSM-3/MDP BALI/X/2010 - I Ketut bakuh; Kadek Endra Setiawan (Jurnal Yustitia, 2026)
The emergence of attention to gender issues is in line with the shift in the development paradigm that is more open to addressing the roles of men and women in society. This then becomes the basis for overcoming the problem of gender injustice that still occurs in society, especially in Bali. The purpose of writing this scientific journal is intended to better understand the development of gender thoughts in the Balinese region through real actualization in everyday life and changes in the inheritance system. This research method is a normative research method with a statutory approach, sociological approach, and conceptual approach. The result of this research is the development of gender equality in several sectors of Balinese life in modern times has provided a positive wind characterized by increased participation of Hindu-Balinese women in several sectors. The issuance of the Keputusan Pesamuhan Agung MUDP Bali Nomor 01/KWP/PSM-3/MDP Bali/X/2010 dated October 15, 2010 concerning the Results of the Great Pesamuhan III of the Main Assembly of Desa Pakraman Bali, shows that in general the customary inheritance law for Balinese Hindu women can be said to have experienced a lot of progress and lead to gender equality.